Morphometric evaluation of the astrocytes reactivity in preterm and term infants with infectious diseases - S. V. Barashkova (Журнал инфектологии, 2014)
Objective: the aim of our work is to describe a condition of the reactive astrocytes in the white matter in preterm and term infants with infectious diseases.Materials and methods: postmortem investigation of periventricular white matter performed on material from 56 children, 35 of them were born preterm (24–36 weeks gestation).Twenty-five children diagnosed with various infectious diseases, other have had clinical signs of hypoxic-ischemic brain injury. Immunohistochemical expression of glial fibrillary acidic protein was used as a marker for reactive astrocyte. We estimated the degree of the astrocytes reactivity, according to the mean percentage of the marker expression in anterior and posterior horns of the lateral ventricles: stage 0 – 0–1,4%, I stage – 1,5–6%, II stage – 6,1–15%, III stage – above 15,1%.Results: comparison of the morphometric marks of the white matter showed no significant differences between groups with infections and hypoxic pathology. In 54.84% of children born at 24–33 weeks gestation determined weak stage of astroglial reactivity. Whereas due to maturation of astrocytes in children born after 34 weeks of gestation more common moderate and severe stages of astrocytes reactivity (collectively, 69,6%) was detected. Severe stage of the reactive astrocytes accompanied by the development of necrotic lesions in the periventricular white matter in 64,3% of cases, in our opinion, as a result of progressive degenerative process in glial cells. The remaining cases relates to the severe telencephalic leukoencephalopathy, perhaps some of them may contain undiagnosed necrosis outside of the white matter regions estimated in our study.Conclusion: morphometric study of the periventricular white matter using a marker of astrocytes allows to assess their reactive changes and to perform differential diagnosis of main forms of white matter injury in infants.